2016
DOI: 10.1017/s0031182015001985
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autophagy interferes the tachyzoite to bradyzoite transformation ofToxoplasma gondii

Abstract: Autophagy process in Toxoplasma gondii plays a vital role in regulating parasite survival or death. Thus, once having an understanding of certain effects of autophagy on the transformation of tachyzoite to bradyzoite this will allow us to elucidate the function of autophagy during parasite development. Herein, we used three TgAtg proteins involved in Atg8 conjugation system, TgAtg3, TgAtg7 and TgAtg8 to evaluate the autophagy level in tachyzoite and bradyzoite of Toxoplasma in vitro based on Pru TgAtg7-HA tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Unlike bulk degradation of the packaged cargo in nonselective autophagy, xenophagy imparts selectivity to the degradation process by tagging and targeting cargoes into lysosomes (17). In mammalian species, the role of xenophagy in selectively eliminating disease-related pathogens, such as mycobacteria (19), HIV (46), and toxoplasma (49), has been well studied. However, the differential regulation mechanisms of xenophagy in response to different microbe challenges in a specific species, particularly an aquatic animal, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike bulk degradation of the packaged cargo in nonselective autophagy, xenophagy imparts selectivity to the degradation process by tagging and targeting cargoes into lysosomes (17). In mammalian species, the role of xenophagy in selectively eliminating disease-related pathogens, such as mycobacteria (19), HIV (46), and toxoplasma (49), has been well studied. However, the differential regulation mechanisms of xenophagy in response to different microbe challenges in a specific species, particularly an aquatic animal, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors and mechanisms governing the interconversion are poorly understood at the molecular level. Studies investigating the switch between the tachyzoite and bradyzoite have confirmed that the SAG1-related sequence (SRS) [27], zinc finger protein (ZFP1) [51], cyclic AMP-dependent protein kinase subunit 3 (PKAc3) [48], mitogen-activated protein kinase 1 (MAPK1) [7], and autophagy-related proteins (Atg) [29] are all involved in bradyzoite differentiation. In the present study, the transcriptional level of the Hsp90 gene was determined when T. gondii cells were under stress at 41 °C or pH 8.1.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the upregulation of host autophagy pathway is reported to inhibit T. gondii growth ( Lee et al., 2020 ). Interestingly, the induction of T. gondii intrinsic autophagy activity has also been shown to interfere with tachyzoite to bradyzoite transformation ( Li et al., 2016 ). PE and UA are known to harbor autophagy-inducing activity ( Ryu et al., 2016 ; Tan et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%